2018
DOI: 10.2739/kurumemedj.ms651004
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a Bifid Mandibular Canal Containing a Large Vein Draining into the Anterior Jugular Vein

Abstract: The bifid mandibular canal (BMC) is an anatomical variant of the mandible that is often observed on cone-beam computed tomographic images. We identified a BMC during routine cadaveric dissection. The upper mandibular canal contained the inferior alveolar nerve and artery, and the lower mandibular canal contained a large inferior alveolar vein. This latter vein left the mandible through a lateral lingual foramen and joined the anterior jugular vein. Additionally, this vein gave rise to small tributaries to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 9 publications
(10 reference statements)
0
7
0
Order By: Relevance
“…Correr et al (2013) demonstrated that when third molars were present, half of their cases showed an intimate relationship, and almost one third a close relationship, between the roots of the third molar and the bifurcation of the mandibular canal. However, as described by Eliades et al (2016) (Iwanaga et al, 2018). Mizbah et al (2012) adopted a different surgical approach when a bifurcation was observed.…”
Section: Failure Of Local Anesthesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Correr et al (2013) demonstrated that when third molars were present, half of their cases showed an intimate relationship, and almost one third a close relationship, between the roots of the third molar and the bifurcation of the mandibular canal. However, as described by Eliades et al (2016) (Iwanaga et al, 2018). Mizbah et al (2012) adopted a different surgical approach when a bifurcation was observed.…”
Section: Failure Of Local Anesthesiamentioning
confidence: 99%
“…Their case involved a supplementary canal that coursed towards the periapical lesion of a third molar, with the tooth successfully removed. Nevertheless, one should be cautious of the risk of hemorrhage, since Iwanaga and colleagues reported a large vein from the accessory canal that drained into the anterior jugular vein (Iwanaga et al, ). Mizbah et al () adopted a different surgical approach when a bifurcation was observed.…”
Section: The Clinical Significance Of Accessory Mandibular Canalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other types are normal branches of the MC. The BMC can accommodate a part of the IAN or even only veins [15]. During our investigation, we did not find any trifid mandibular canal in previous studies that satisfy our criteria; two additional intramandibular canals running parallel to the mandibular canal with/without confluence to the main canal.…”
Section: What Is a Bifid Mandibular Canal?mentioning
confidence: 54%
“…Tis French embryologist examined the vein, in one additional mandibular canal, draining below main canal [2]. Tis canal was confrmed by one recent cadaver report [3], but the authors did not report it as Serres's canal. Also, one human embryonic study [4] corroborated the existence of Serres's vein draining both pterygoid venous plexus posteriorly and venous plexus at mandibular symphysis anteriorly along with Meckel's cartilage (Figure 1(d)) of human embryo.…”
Section: Introductionmentioning
confidence: 99%